Gold-catalyzed propargylic substitutions: Scope and synthetic developments - Debleds, Olivier; Gayon, Eric; Vrancken, Emmanuel; Campagne, Jean-Marc (Beilstein Journal of Organic Chemistry, 2011)
This personal account summarizes our recent developments in gold-catalyzed direct substitutions on propargylic (allylic, benzylic) alcohols, with various nucleophiles (and bi-nucleophiles) based on the σ- and/or π-acidity of gold(III) complexes. Synthetic developments are also briefly described.
Keywords: direct substitutions; gold; isoxazolines; propargylic substitutions